2021
DOI: 10.2147/bctt.s289014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of AC and AC-T Chemotherapy’s Toxicities on Quality of Life Among Women with Breast Cancer in Ethiopia: A Prospective Patient-Reported Outcomes Study

Abstract: Purpose The study aimed to evaluate the quality of life patterns and the effects of AC and AC-T chemotherapy’s toxicities on QoL among Ethiopian women with breast cancer. Methods QoL was measured at baseline and at every end of two cycles, for the median of 8 cycles among 146 breast cancer women on AC and AC-T chemotherapy, using EORTC QLQ-C30 and BR23 instruments. The effect of QoL score, socio-demographic, and clinical variables at baseline were adjusted for the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…A similar pattern of results was demonstrated in a previous study wherein global health status was declined after cycle 2 of the conventional chemotherapy. Likewise, cognitive functioning, emotional functioning, social functioning, role functioning, and physical functioning of the patients were signi cantly deteriorated during the rst two cycles of chemotherapy [41]. Akin, et al reported that all quality of life dimensions were negatively affected in Turkish breast cancer patients undergoing chemotherapy [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar pattern of results was demonstrated in a previous study wherein global health status was declined after cycle 2 of the conventional chemotherapy. Likewise, cognitive functioning, emotional functioning, social functioning, role functioning, and physical functioning of the patients were signi cantly deteriorated during the rst two cycles of chemotherapy [41]. Akin, et al reported that all quality of life dimensions were negatively affected in Turkish breast cancer patients undergoing chemotherapy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nancial di culties were signi cantly worse in patient taking conventional chemotherapy when compared with patients on HER2targeted therapy. Gadisa et al reported that QOL of patients with breast cancer was negatively affected by chemotherapy's side effects such as fatigue, constipation, dry mouth, vomiting, oral mucositis, skin hyperpigmentation and peripheral neuropathy [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that the toxicity profile of tamoxifen and aromatase inhibitors did not show significant reduction in the overall QOL [44]. Gadisa et alreported that QOL of patients with BC was adversely affected by chemotherapy's side effects [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients on HER2-targeted therapy had 10.2 times chances to get good QOL than patients on conventional chemotherapy. A previous study demonstrated that systemic side effects of conventional chemotherapy (oral mucositis, constipation, peripheral neuropathy, anemia arthralgia/myalgia, dry mouth, diarrhea, constipation, and skin hyperpigmentation) were predictors for deteriorated QLQ [39].…”
Section: Discussionmentioning
confidence: 99%